2012
DOI: 10.1371/journal.pone.0047755
|View full text |Cite
|
Sign up to set email alerts
|

Human Papillomavirus Infection in HIV-1 Infected Women in Catalonia (Spain): Implications for Prevention of Cervical Cancer

Abstract: BackgroundHigh-risk human Papillomavirus infection is a necessary factor for cervical squamous intraepithelial lesions and invasive cervical cancer. In HIV-1-infected women, HPV infection is more prevalent and a higher risk of cervical cancer has been identified. We aimed to calculate the prevalence of infection by HR-HPV, determine the factors associated with this infection and abnormal cytology findings and to describe the history of cervical cancer screening in HIV-1-infected women.MethodsWe enrolled 479 HI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
20
3
3

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 27 publications
6
20
3
3
Order By: Relevance
“…The screening coverage found in the present study is considerably lower than what have been published in previous studies reporting a coverage to the annual ICC HIV screening program between 51% and 81% [13,14,16,30]. These studies are based on self-reported data, and the difference might reflect that women tend to over-report their participation in cervical screening in a given timeframe and therefore these rates are likely upper-end estimates [31].…”
Section: Discussioncontrasting
confidence: 81%
“…The screening coverage found in the present study is considerably lower than what have been published in previous studies reporting a coverage to the annual ICC HIV screening program between 51% and 81% [13,14,16,30]. These studies are based on self-reported data, and the difference might reflect that women tend to over-report their participation in cervical screening in a given timeframe and therefore these rates are likely upper-end estimates [31].…”
Section: Discussioncontrasting
confidence: 81%
“…In general, throughout the study period, the authors analysed different time intervals, with the range of HIV-positive women who followed the HIV cervical screening guidelines being from 29% to 46%. Compared with the above, a multicentre Catalan study revealed inadequate rates of cervical cancer screening with only 50% of HIV positive women reporting that they had annual screening [15]. It is worth mentioning that in a prospective study of HPV infection among HIV positive women from European countries with a study population of over IDU -injected drug users; CI -confidence interval; OR -odds ratio 1100 women, only 55.5% provided a second sample after 6 or more months [3].…”
Section: Discussionmentioning
confidence: 93%
“…However, data coming from observational studies in Europe, although scarce, shows that barriers to cervical cancer screening still exist, from both the patient's and the health system's perspectives [14,15,20]. It is important to note that according to a recently published EuroSIDA study of a pan-European longitudinal observational cohort, cancer screening has a low coverage in both Eastern and non-Eastern European countries [21].…”
Section: Discussionmentioning
confidence: 99%
“…In HIV-infected subjects, oral HPV infection is more aggressive and more highly prevalent compared with a healthy population161922. A comparative study including HIV-infected patients and healthy subjects foundthat 25.3% of HIV patients had an HPV infection in the oral tractcompared with 7.6% of healthy subjects23.…”
Section: Discussionmentioning
confidence: 99%